A two degrees of freedom permanent magnet conical motor - Roggia, Sara (2018)
This thesis focuses on the development of an innovative, electrical machine topology, which is based around a permanent magnet, synchronous machine that comprises a conical shape in order to achieve a two degrees of freedom machine. Such a machine is able to produce the rotational torque while also allowing for controlled movement in the axial direction. The proposed topology combines the high-performance capabilities of a permanent magnet machine with the desired axial movement that can be capitalised upon in order to remove traditional clutching-declutching technologies.